2022
DOI: 10.3892/br.2022.1574
|View full text |Cite
|
Sign up to set email alerts
|

Role of hyaluronic acid in periodontal therapy (Review)

Abstract: Hyaluronic acid (HA) is essential for the function of extracellular matrices in both hard and soft periodontal components. HA plays an important role in the mechanisms underlying inflammation and wound healing. HA is located in periodontal tissues in differing amounts, including non-mineralized tissues, such as gingiva and periodontal ligament, and lower levels located in mineralized tissues, such as cementum and alveolar bone. According to preliminary findings, HA exhibits potential in the regulation of perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
10
0
3
Order By: Relevance
“…The significant improvement of gingival (GI and BOP) and periodontal (PPD and CAL) parameters in the HA group may have been due to the anti-inflammatory effects of the HA gel. The subgingival administration of the HA gel resulted in a reduction in prostaglandins, matrix metalloproteinases, and bioactive materials that led to a lessening of tissue destruction and promotion of periodontal tissue healing [ 25 ]. The present findings are similar to the results obtained by Al Shammari et al [ 26 ], who reported that the mean values of clinical parameters (GI, PPD, and CAL) were improved in both test groups (scaling and root planing (SRP + 0.8% HA gel)) and control group (SRP alone) but with more improvement in the SRP + HA group [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The significant improvement of gingival (GI and BOP) and periodontal (PPD and CAL) parameters in the HA group may have been due to the anti-inflammatory effects of the HA gel. The subgingival administration of the HA gel resulted in a reduction in prostaglandins, matrix metalloproteinases, and bioactive materials that led to a lessening of tissue destruction and promotion of periodontal tissue healing [ 25 ]. The present findings are similar to the results obtained by Al Shammari et al [ 26 ], who reported that the mean values of clinical parameters (GI, PPD, and CAL) were improved in both test groups (scaling and root planing (SRP + 0.8% HA gel)) and control group (SRP alone) but with more improvement in the SRP + HA group [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hyaluronic acid‐based products are now emerging as a clinically relevant treatment alternative due to the material's intrinsic regenerative potential. [ 210 ] However, the clinical trial by Pilloni et al demonstrated that the performance of hyaDENT BG falls short of that of Emdogain. [ 222 ] Furthermore, there is currently no study comparing the efficacy of Gengigel to Emdogain.…”
Section: Discussionmentioning
confidence: 99%
“…[216] Scientific evidence supports the topical application of these gels for treating gingivitis, and for non-surgical and surgical periodontitis treatment. [207,210,[217][218][219] HyaDENT BG: HyaDENT BG (Bioscience GmbH, Germany) is a hydrogel formulation containing biotechnologically produced synthetic hyaluronic acid (MW = 1000 kDa) cross-linked with butanediol diglycidyl ether (BDDE) and noncrosslinked hyaluronic acid (MW = 2500 kDa) in a ratio 8:1 to a total concentration of 18 mg mL −1 . [149,220,221] The adjunct of cross-linked hyaluronic acid slows down the resorption rate of the gel, making it suitable for clinical use.…”
Section: Hyaluronan-based Hydrogelsmentioning
confidence: 99%
“…Dažnai naudojami antibiotikai bei antiseptikai, tokie kaip chlorheksidinas, cetilpiridinas ir vandenilio peroksidas, taip pat medžiagos, kurios gali padėti gijimui ir audinių regeneracijai, pavyzdžiui, emalio matricos baltymai ar hialurono rūgštis Tyrimo tikslas -atlikti mokslinės literatūros apžvalgą apie hialurono rūgštį ir jos terapinį poveikį gydant periodonto bei periimplantines ligas. [6]. Burnoje mineralizuotuose kraštinio kaulo ir šaknies cemento audiniuose HR yra labai mažai, tačiau dantenose bei periodonto raištyje šios medžiagos gausu [7].…”
Section: įVadasunclassified
“…Burnoje mineralizuotuose kraštinio kaulo ir šaknies cemento audiniuose HR yra labai mažai, tačiau dantenose bei periodonto raištyje šios medžiagos gausu [7]. HR pusinės eliminacijos laikas svyruoja nuo 12 valandų iki 2-3 dienų [6].…”
Section: įVadasunclassified